An Air Traffic Controller Action Extraction-Prediction Model Using Machine Learning Approach. (18th November 2020) - Pham, Duc-Thinh; Alam, Sameer; Duong, Vu
Abstract : In air traffic control, the airspace is divided into several smaller sectors for better management of air traffic and air traffic controller workload. Such sectors are usually managed by a team of two air traffic controllers: planning controller ( D -side) and executive controller ( R -side). D -side controller is responsible for processing flight-plan information to plan and organize the flow of traffic entering the sector. R -side controller deals with ensuring safety of flights in their sector. A better understanding and predictability of D -side controller actions, for a given traffic scenario, may help in automating some of its tasks and hence reduce workload. In this paper, we propose a learning model to predict D -side controller actions. The learning problem is modeled as a supervised learning problem, where the target variables are D -side controller actions and the explanatory variables are the aircraft 4D trajectory features. The model is trained on six months of ADS-B data over an en-route sector, and its generalization performance was assessed, using crossvalidation, on the same sector. Results indicate that the model for vertical maneuver actions provides highest prediction accuracy (99%). Besides, the model for speed change and course change action provides predictability accuracy of 80% and 87%, respectively. The model to predict the set of all the actions (altitude, speed, and course change) for each flight achieves an accuracy of 70% implying for 70% of flights; D -side controller's action can be predicted from trajectory information at sector entry position. In terms of operational validation, the proposed approach is envisioned as ATCO assisting tool, not an autonomous tool. Thus, there is always ATCO discretion element, and as more ATCO actions are collected, the models can be further trained for better accuracy. For future work, we will consider expanding the feature set by including parameters such as weather and wind. Moreover, human in the loop simulation will be performed to measure the effectiveness of the proposed approach.